Which Are the Most Relevant Questions in the Assessment of Outcome after Distal Radial Fractures? - Donald Buchanan; D. Prothero; J. Field (Advances in Orthopedics)
A study was designed to determine which wrist scoring system best correlates with patient satisfaction and which individual variables predict a satisfactory outcome. We looked at forty-five females and 5 males with wrist fractures at 12 weeks after injury and compared their level of satisfaction with various respected outcome measures. The mean age was 66 years. Multivariate regression analysis was carried out using a statistical software package. Patient satisfaction correlated best with the MacDermid, Watts, and DASH scores. The variables in these scoring systems that predicted satisfaction were pain and ability to perform household chores or usual occupation, open packets, and cut meat. The four most important questions to ask in the clinic following wrist fractures are about severity of pain and ability to open packets, cut meat, and perform household chores or usual occupation. This may provide simple and more concise means of assessing outcome after distal radial fractures. Level of evidence is level 4.